Estudo sobre estabelecimento de gramíneas forrageiras - Marques Gontijo, Roberto; Alberto Gomide, José; J Sykes, Dwane; Vilela, Herbert (Revista Ceres, 2025)
Anexperiment was conducted ona weedy molassesgrass pasture growing onan acid, low fertility soil in order to compare methods of soil preparation and chemical fertilization on es- tablishment of pangolagrass (Digitaria decumbens Stent.), suwanee bermudagrass (CynodondactylonPers) or molassesgrass (Melinis minutiflora Beauv. ).